Alginate, elastase and alkaline protease production of Pseudomonas aeruginosa strains isolated from various body sites [Çeşitli vücut bölgelerinden izole edilen Pseudomonas aeruginosa suşlarinin aljinat, elastaz ve alkali proteaz üretimleri] - (:unkn) unknown (My University, 2004)
In this study, alginate, elastase and alkaline protease production of Pseudomonas aeruginosa, which are accepted as virulence factors, have been investigated in the strains isolated from 60 lower respiratory tract samples of cystic fibrosis patients, together with the strains isolated from 59 lower respiratory tract, 62 urine and 32 blood samples of non-cystic fibrosis patients, in order to evaluate the relationship between the virulence factors and infected body sites. Our results indicated that all isolates including the ones from cystic fibrosis patients produced similar levels of alginate ranging between 1.830±1.666 and 1.305±1.690 μg/ml with the exception of urinary isolates for which the alginate amount was 0.9655±1.386 (p<0.05). Elastase levels exhibited no statistically significant difference among groups of isolates; and finally alkaline protease levels, although not statistically significant, was greater in urine isolates than blood and respiratory isolates; however, it was significantly lower in cystic fibrosis isolates compared to the remaining three groups (p<0.05). It can be concluded that alginate, elastase and alkaline protease levels do not differ when different body sites are considered. However, it was observed that alkaline protease was the least produced virulence factor in terms of different body sites. Alginate was found to be the most commonly produced virulence factor in respiratory tract isolates, regardless of presence of cystic fibrosis.
Keywords: Alginate; Alkaline protease; Elastase; Pseudomonas aeruginosa